The Effect of Learning Method and Cognitive Styles on the Ability to Write Descriptive Text - Syamsul Irfan (Program Studi Magister Linguistik Terapan UNJ, 2017)
The objective of this research is to fine out the effect of Learning method and cognitive styles on the ability to write descriptive text. The research was conducted at the department of English education STKIP Hamzanwadi Selong East Lombok West Nusa Tenggara. in the 2014/2015 academic year. The population was the second semester. The sample size was 70 students.The method used in this study was an experimental method by using factorial design 2X2. The data were analyze by using a two-factorial ANAVA at the significance level α 0,05. In this design, Learning method as a treatment consisting of inquiry method and modeling method, while the cognitive styles consists of field-independent (FI) and filed-dependent (FD), this research findings are: (1) the ability of writing descriptive text the group of students who learned with inquiry methods is higher than those who learned with modeling method; (2) the ability of writing descriptive text of the group of students who has filed-independent cognitive style is higher than those who have filed-dependent cognitive style; (3) there is an interaction effect between Learning method and the cognitive styles on the writing English descriptive text; (4) the ability of writing descriptive text of the students who learned with inquiry method is higher than those who learned with modeling method, for the group who have field-independent cognitive styles; (5) the ability of writing descriptive text of the students who learned whit modeling method is higher than those who learned with inquiry method, for the group who have field-dependent cognitive styles